2015
DOI: 10.1590/1519-6984.07813
|View full text |Cite
|
Sign up to set email alerts
|

Translocation and radio-telemetry monitoring of pygmy marmoset, Cebuella pygmaea (Spix, 1823), in the Brazilian Amazon

Abstract: Two groups of pygmy marmoset (Cebuella pygmaea) were rescued along the left bank of the Madeira River during the formation of Santo Antônio Hydroelectric Dam reservoir in the state of Rondônia, Northern Brazil. Reintroduction of both groups occurred in areas of open Tropical rainforest located within the project´s Permanent Preservation Area. A post-release monitoring was conducted for three months using radio-telemetry. Individuals of each group remained together and settled in stable home ranges near their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Rodent translocations showed a large discrepancy between the conservative (4.3%) and inclusive (31.5%) estimates of incidence. Hyperdispersal in primate translocations varied considerably from up to 100% in smaller primates (Dias et al., 2015) to just 2% of translocated gorillas (King et al., 2012). Projects trended toward small sample sizes, due to social dependency (Dias et al., 2015; Richard‐Hansen et al., 2000) and limited stock (King et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rodent translocations showed a large discrepancy between the conservative (4.3%) and inclusive (31.5%) estimates of incidence. Hyperdispersal in primate translocations varied considerably from up to 100% in smaller primates (Dias et al., 2015) to just 2% of translocated gorillas (King et al., 2012). Projects trended toward small sample sizes, due to social dependency (Dias et al., 2015; Richard‐Hansen et al., 2000) and limited stock (King et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Hyperdispersal in primate translocations varied considerably from up to 100% in smaller primates (Dias et al., 2015) to just 2% of translocated gorillas (King et al., 2012). Projects trended toward small sample sizes, due to social dependency (Dias et al., 2015; Richard‐Hansen et al., 2000) and limited stock (King et al., 2012). Many reintroductions used animals sourced from captivity, such as rescues from the illegal wildlife trade (Osterberg et al., 2015), so hyperdispersal rates may not be representative of wild‐sourced translocations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…De Sá (2004 observed an increase in the population density of Plecturocebus, Pithecia, and Samiri in the adjacent habitat just after the release, but an abrupt decrease in the same in subsequent years. Another example, also in Brazil, reports a telemetry follow-up that found that only 7% translocated Cebuella pygmaea survived 3 months after release (Dias et al, 2015).…”
Section: Implications For the Conservation Of Alouatta Carayamentioning
confidence: 99%